Factors Predicting Safety Management Competencies among Professional Nurses at Hospital in Samut Sakhon Province - เสียงอ่อน, ลัดดาวรรณ; Chonthong, Rattana; Kawinsuporn, Porntip (NU Journal of Nursing and Health Sciences, 2023)
The purposes of this descriptive research were to determine the predicting factors in the safety management competencies of professional nurses. A simple random sampling data were obtained 153 persons of professional nurses at hospital, Samut Sakhon province. The research instrument consist of; (1) The demographic data questionnaires; (2) The predicting factors for the safety management competencies of professional nurses questionnaires, Content Validity Index (CVI) = 0.98; (3) The safety attitude questionnaires, CVI = 0.96; (4) The organizational climate questionnaires, CVI = 0.97; and (5) The empowerment squestionnaires, CVI = 1.00. The data was statistic analyzed by using percentage (%) , average ( ), standard deviation (S.D.), and linear regression. Finding show that mean and standard deviation scores of the results indicated that the safety management competencies of professional nurses at hospital of Samut Sakhon province were at the high level ( = 3.69, S.D. = 0.52), the safety attitudes were at the high level ( = 3.92, S.D. = 0.46), the precision of the organizational climates were at the high level ( = 3.86, S.D. = 0.53), and the precision of the empowerments were at the high level ( = 3.71, S.D. = 0.56). These findings support the relationship betaween the safety management competencies of professional nurses and the empowerments were significantly (r = .682, P < .01), the predictable of the safety management competencies of professional nurses was 46.50% (SE est + 3.884, R = 0.682 , R2 = 0.465, F = 129.503, p = .000), and the predictive equation was: Safety Management Competencies of Professional Nurses = 1.336 + 0.637 of Empowerment. The researchers suggested that the nursing leaders should be establish the policy or the guildline of the empowerment for the professional nurses, which they could work effectively for the safety managments in their organizations.